Calibration of Air Quality Data Based on Multiple Regression Model. Issue 3 (May 2020) - Zhang, Hanping
Abstract: According to the data of question D's Annex 1 and Annex 2 of the National University Student Modeling Contest 2019, the correlation between the 6 air quality data errors and 5 meteorological factors at the self-built station is obtained by using the gray correlation method. Using the multiple linear regression method, and making the difference between the air quality data of the self-built station and the national control station as the dependent variable, and the meteorological data of the self-built station as the independent variables, six multiple regression equations were established to correct the air quality data of the self-built station.